Clinical application of ultrasound-guided platelet-rich plasma gel in the treatment of supraspinatus tendon tears: a single-center retrospective study - Huajun Xu; Jianfei Zhou; Huimei Zhang (Scientific Reports)
Abstract To explore the clinical significance of ultrasound-guided platelet-rich plasma (PRP) gel in the treatment of supraspinatus tendon tears. 82 patients with mild or moderate supraspinatus tendon tears were divided into three groups and were administered with different treatments. VAS scores, Constant-Murley scores, fat infiltration, as well as the treatment efficacy and incidence of adverse reactions were evaluated. At 3 months postoperatively, PRP gel group (2.07 ± 0.52 vs. 2.80 ± 0.85, t = 3.84, P = 0.0003) and PRP group (2.33 ± 0.55 vs. 2.80 ± 0.85, t = 2.33, P = 0.02) showed lower VAS scores than sodium hyaluronate group. At 6 months postoperatively, the PRP gel group revealed significantly lower VAS scores than both PRP group (2.13 ± 0.57 vs. 2.67 ± 0.71, t = 3.07, P = 0.003) and sodium hyaluronate group (2.13 ± 0.57 vs. 3.17 ± 1.02, t = 4.67, P < 0.0001). At 3 and 6 months postoperatively, the PRP gel group exhibited statistically higher Constant-Murley scores compared to both the PRP and sodium hyaluronate groups (P < 0.05). At 6 months after surgery, musculoskeletal ultrasound revealed that PRP gel and PRP groups displayed lower fat infiltration in the supraspinatus muscle than those in sodium hyaluronate group (1.86 ± 0.52 vs. 1.96 ± 0.64 vs. 2.32 ± 0.55, F = 5.06, P = 0.008). Additionally, at this time point, efficacy rate for patients in PRP gel group was significantly higher than that observed in either PRP group or sodium hyaluronate group (93.10% vs. 80.77% vs. 66.67%, χ2 = 6.14, P = 0.01). In conclusion, ultrasound-guided PRP gel treatment can not only improve pain and joint function but also decrease fat infiltration, thereby enhancing treatment efficacy for supraspinatus tendon tears.